2020
DOI: 10.4236/ce.2020.114041
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Existence of “Teaching to the Test” at SSC Level in Bangladesh

Abstract: The paper aims at examining the influence of Secondary School Certificate (SSC) English language test on teaching in the existing CLT-based teaching context in Bangladesh. It is a fact that SSC test results continue to influence the total educational career of a student including his admission into Higher Secondary Certificate (HSC) level and subsequently at tertiary level study. Later on, SSC result is one of the vital determinants of his employment. As a result, the washback effect i.e. effect of test (SSC E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Instead, the standards of English have degraded over the last few years rather than showing evidence of improvement. Some studies (Jamila & Kabir 2020;Islam, 2015;Rahman, 2015) have suggested a strong presence of teaching to the test in teachers' classroom practices. Classroom English teachers are responsible for designing various internal examinations, and a few of them even serve on examination boards as question setters.…”
Section: Research Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the standards of English have degraded over the last few years rather than showing evidence of improvement. Some studies (Jamila & Kabir 2020;Islam, 2015;Rahman, 2015) have suggested a strong presence of teaching to the test in teachers' classroom practices. Classroom English teachers are responsible for designing various internal examinations, and a few of them even serve on examination boards as question setters.…”
Section: Research Contextmentioning
confidence: 99%
“…It was expected that post CLT era of English language teaching and learning outcome would be better in terms of developing language proficiency among the learners. Host of studies (Hamid & Baldauf, 2008;Kabir, 2008;Kabir, 2009;Jamila & Kabir, 2020) show that CLT is not as effective as it was thought of in the context of Bangladesh. The quality of English language teaching and testing at Primary, Secondary and Higher Secondary levels is questioned by a host of researchers (Kabir, 2015a(Kabir, , 2015bBillah, 2015;Mariyam et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For the sake of greater validity and reliability of this research, we used classroom teaching observation and teacher interview to investigate the ways how (SSC) test influences teaching Cheng, 2005;Wall, 2005. and Yi-Ching Pan 2013 suggest that it is crucial to combine asking which in-questionnaires, and watching i.e.…”
mentioning
confidence: 99%